THE EFFECT OF PRICE AND SERVICE QUALITY ON CONSUMER SATISFACTION BY EMPLOYING MARKETING RELATIONSHIPS AS INTERVENING VARIABLES - Ni Nyoman Sawitri; Pande Putu Buda Prasada (Dinasti Publisher, 2022)
This study aims to determine the effect of service quality and price on consumer satisfaction by using marketing relationships as an intervening variable. This is quantitative research. The data presented in this study were obtained through a questionnaire given to 50 respondents. The research design used in hypothesis testing is the structural equation model (SEM) – Smart PLS The results of this study indicate that: (1) There is a significant direct effect of service quality on consumer satisfaction, (2) There is a significant direct effect of price on customer satisfaction, (3) There is a significant direct effect of service quality on marketing relationship, (4) There is a significant direct effect of price on marketing relationship, (5) There is a significant indirect effect of service quality, price and marketing relationship that can be a mediator on consumer satisfaction.